Longitudinal social cognitive influences on physical activity and sedentary time in Hispanic breast cancer survivors. Issue 2 (25th November 2015) - Mama, Scherezade K.; Song, Jaejoon; Ortiz, Alexis; Tirado‐Gomez, Maribel; Palacios, Cristina; Hughes, Daniel C.; Basen‐Engquist, Karen
Abstract: Objective: This study evaluated the effect of two home‐based exercise interventions (one culturally adapted and one standard) on changes in social cognitive theory (SCT) variables, physical activity (PA), and sedentary time (ST), and determined the association between changes in SCT variables and changes in PA and ST in Hispanic breast cancer survivors. Method: Project VIVA! was a 16‐week randomized controlled pilot study to test the effectiveness and feasibility of a culturally adapted exercise intervention for Mexican American and Puerto Rican breast cancer survivors in Houston, Texas and San Juan, Puerto Rico, respectively. Women ( N = 89) completed questionnaires on SCT variables, PA, and ST and were then randomized to a 16‐week culturally adapted exercise program, a non‐culturally adapted standard exercise intervention or a wait‐list control group. Multiple regression models were used to determine associations between changes in SCT variables and changes in PA and ST. Results: Participants were in their late 50s (58.5 ± 9.2 years) and obese (31.0 ± 6.5 kg/m 2 ). Women reported doing roughly 34.5 min/day of PA and spending over 11 h/day in sedentary activities. Across groups, women reported significant increases in exercise self‐efficacy and moderate‐intensity, vigorous‐intensity, and total PA from baseline to follow‐up ( p < 0.05). Increased social support from family was associated with increases in vigorous‐intensity PA. Increases in social modeling were associated with increases in moderate‐intensity and total PA and with decreases in ST from baseline to follow‐up ( p < 0.05). Conclusions: Hispanic cancer survivors benefit from PA interventions that focus on increasing social support from family and friends and social modeling. Copyright © 2015 John Wiley & Sons, Ltd.